Detecção de vasos sanguineos em imagens de fundo de olhos - PAIVA JÚNIOR, Sérgio de Sá Leitão (2016)
Submitted by (ana.araujo@ufrpe.br) on 2016-08-12T15:12:18Z No. of bitstreams: 1 Sergio de Sa Leitao Paiva Junior.pdf: 1027714 bytes, checksum: 382b44b0daa25e3bc9eed83acf4e7b18 (MD5)